Fractal analysis reveals subclasses of neurons and suggests an explanation of their spontaneous activity. (28th July 2016) - Favela, Luis H.; Coey, Charles A.; Griff, Edwin R.; Richardson, Michael J.
Highlights: Dynamics of single neurons in an anesthetized animal model were analyzed via fractal methods. Detrended fluctuation analysis (DFA), a kind of fractal analysis, was utilized to bolster the case for two subclasses of mitral cells. Fractal methods (DFA) captured differences in dynamics at longer time scales between two groups of neurons; a difference not revealed by standard statistical methods. One group of neurons demonstrated dynamics in the 1/ f spectrum. Self-organized criticality is one explanation of dynamics that fall within the 1/ f spectrum, and is thus a potential mechanism driving the spontaneous activity of particular classes of neurons. Abstract: The present work used fractal time series analysis (detrended fluctuation analysis; DFA) to examine the spontaneous activity of single neurons in an anesthetized animal model, specifically, the mitral cells in the rat main olfactory bulb. DFA bolstered previous research in suggesting two subclasses of mitral cells. Although there was no difference in the fractal scaling of the interspike interval series at the shorter timescales, there was a significant difference at longer timescales. Neurons in Group B exhibited fractal, power-law scaled interspike intervals, whereas neurons in Group A exhibited random variation. These results raise questions about the role of these different cells within the olfactory bulb and potential explanations of their dynamics. Specifically, self-organized criticality has been proposed as an explanation of fractal scaling in many natural systems, including neural systems. However, this theory is based on certain assumptions that do not clearly hold in the case of spontaneous neural activity, which likely reflects intrinsic cell dynamics rather than activity driven by external stimulation. Moreover, it is unclear how self-organized criticality might account for the random dynamics observed in Group A, and how these random dynamics might serve some functional role when embedded in the typical activity of the olfactory bulb. These theoretical considerations provide direction for additional experimental work.